Accessibility of Information and Communication Technology Services by Faculty Members of a State Agricultural University - Haqyar, Ziaulhaq; Rohila, Anil Kumar; Mukteshawar, Rati; Sheokand, Ram Niwas (Indian Journal of Extension Education, 2022)
The research was carried out at the CCS Haryana Agricultural University, Hisar in 2021- 22 to assess the availability and accessibility of information and communication technology services among faculty members. Data was collected with the help of well-structured questionnaire and analysed using Statistical Package for the Social Sciences (SPSS). 25 faculty members were selected randomly from four purposively selected college of CCSHAU, Hisar. Study concluded that all of respondents had computer/laptop, internet, e-mail, and mobile phone/ telephone facilities available at department/workplace. Majority of the respondents also had printer (97.00%), scanner (83.00%), photocopier (77.00%) and LCD projector (74.00%).
Keywords: Agriculture; Digital; Resources and Services